A companion to media fandom and fan studies - Booth, Paul 1981- (Wiley Blackwell companions in cultural studies, 2018)
"A Companion to Media Fandom and Fan Studies offers scholars and fans an accessible and engaging resource for understanding the rapidly expanding field of fan studies. International in scope and written by a team that includes many major scholars, this volume features over thirty especially-commissioned essays on a variety of topics, which together provide an unparalleled overview of this fast-growing field.